Identification of the most common phraseological units in the English language in academic texts: contributions coming from corpora (Acta Scientiarum. Language and Culture, 2017)
Academic-scientific phraseological units in the English language play a key role in the communication of/to experts, once they reproduce frequent and expected expressions in varied disciplines. This paper aims at identifying and analyzing the 100 non-specialized academic-scientific phraseological units (constituted of 4 words) in the English language, present in eight major fields of knowledge. The theoretical background referred to Phraseology and Corpus Linguistics. Regarding methodology, an academic corpus was compiled with more than 120 million words. The software WordSmith Tools was used for the linguistic-textual process. Through the Juilland dispersion coefficient and use coefficient, the most frequent phraseological units were identified in the academic texts. The list was eventually validated by the Wilcoxon rank sum test (Î± = 0.05), indicating that the phraseological units identified show a higher use in the academic communication when compared to the use in the general language. The most relevant units are ‘the case of’, ‘as a result of’ and ‘at the end of’. The list with the most functional phraseological units in the English language might provide a valuable pedagogical linguistic reference for the study of the academic genre.